Safety of endoscopic retrograde cholangiopancreatography in patients 80 years of age and older - Behlül, Baydar; Ayfer, Serin; Sezgin, Vatansever; Altay, Kandemir; Mustafa, Çelik; Cem, Çekiç; Bilge, Örmeci; Fatih, Aslan; Emrah, Alper; Zafer, Buyraç; Kadir, Aksöz; Belkis, Ünsal (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction: Endoscopic retrograde cholangiopancreatography (ERCP) is used in the diagnosis and therapy of biliary tract diseases. The ERCP is an invasive procedure that does not increase complications in the elderly. Few studies have assessed the safety of ERCP in the elderly. Life expectancy is rising, which causes an increasing demand for ERCP in the elderly. Aim: To show that therapeutic ERCP is safe and we compared the level of complications among the elderly (> 80 years of age) and the level among a younger group (< 65 years of age). Material and methods : The study was designed retrospectively. The details of all patients 80 years of age and older undergoing ERCP were analysed. One hundred and fifty patients were included in each of the groups: > 80 years of age, older group A; and < 65 years of age, younger group B. Results : In group A, 4 cases (2.7%) of bleeding (all mild) was observed, and perforation was not observed. The ERCP-related mild pancreatitis was observed in 7 patients (4.6%). There were no cases of mortality during procedures of ERCP in group A. In group B 6 bleeding cases (4%) (all mild) were observed. Perforation was not observed in group B. ERCP-related mild pancreatitis occurred in 11 patients (7.3%). There were no cases of mortality during procedures of ERCP in group B. Our study showed that ERCP is a safe and effective procedure in elderly patients.  Conclusions : Outcomes of ERCP for diagnostic and therapeutic success, and complication rates, are similar to those in younger patients. The ERCP is effective and safe in the elderly.